المنهج النبوي في الوقاية من الجريمة السياسية: المدينة المنورة أنموذجا - طهراوي, علي; أولاد سعيد, أحمد (جامعة الوادي - University of Eloued, 2021)
ملخص: سنتعرض في هذه الدراسة إلى مجتمع المدينة المنورة في عهد رسول الله صلى الله عليه وسلم من خلال بيان الأسس والمبادئ التي قام عليها, وعرض التشريعات والأحكام التي نظمته ووقته من الجرائم عامة، والجريمة السياسية خاصة, ونستنتج من خلالها المنهج النبوي في الوقاية من الجريمة السياسية في المجتمع المدني, الذي يعتبر حاضرة الدولة الإسلامية, وكيف قام صلى لله عليه وسلم ببنائه ودعم ركائزه وتوحيده واستقراره . Abstract : This study investigates the Medina society during the era of the Prophet (Peace Be Upon Him) through eliciting the foundations and principles upon which it was built. It also surveys the legislations and laws that contributed to the regulation and protection of the society from crime in general and political offences in particular. We, through this work, deduce the Prophetic Approach to preventing political crime in the Medina society, which is considered as the metropolis of Islamic state as founded, supported, unified, and stabilized by the Prophet (Peace Be Upon Him).
The Prophetic Approach in Preventing Political Crime: The Case of Medina as a Model
مقال
Keywords: الوقاية ؛ المجتمع؛ الجريمة السياسية؛ المدينة؛ التشريعات; prevention; society; political crime ; medina; legislations